2013
DOI: 10.1002/macp.201300302
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition Separation of EP Copolymers by CEF and HT‐SGIC: Crystallization versus Adsorption

Abstract: Preparative temperature rising elution fractionation (prep TREF) suffers from co‐crystallization effects and, therefore, cannot provide reliable chemical composition distribution (CCD) information. This limitation can be overcome when prep TREF is combined with further fractionation methods such as crystallization elution fractionation (CEF) or high‐temperature solvent‐gradient‐interaction chromatography (HT‐SGIC) as a new approach. By CEF, significant amounts of (co‐crystallizing) amorphous ethylene‐propylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…A comprehensive solvent‐gradient chromatographic technique which permits separation and characterization to occur above the melting and crystallization temperatures of polyolefins has been used to avoid the problems of co‐crystallization effects that take place in DSC, TREF, and CRYSTAF . The recently developed high temperature–high performance liquid chromatography (HT‐HPLC) allows the analysis of both the amorphous and the crystalline fractions since the separation depends on the interaction or adsorption of the macromolecules with the stationary phase . For EPR copolymers it had been reported that on a graphitic stationary phase the separation depends mainly on the ethylene content of the sample .…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive solvent‐gradient chromatographic technique which permits separation and characterization to occur above the melting and crystallization temperatures of polyolefins has been used to avoid the problems of co‐crystallization effects that take place in DSC, TREF, and CRYSTAF . The recently developed high temperature–high performance liquid chromatography (HT‐HPLC) allows the analysis of both the amorphous and the crystalline fractions since the separation depends on the interaction or adsorption of the macromolecules with the stationary phase . For EPR copolymers it had been reported that on a graphitic stationary phase the separation depends mainly on the ethylene content of the sample .…”
Section: Introductionmentioning
confidence: 99%
“…Such methods are still able to separate plastomers with densities between 902 and 910 kg m −3 according to their comonomer contents but are not suitable for elastomers with densities from 900 to 857 kg m −3 . [2][3][4][5] The most significant contribution to the characterization of polyolefins with low crystallinities according to their CCDs has been achieved by interaction liquid chromatography at high temperatures (HTIC), which works at operating conditions above crystallization and melting temperatures and separates complex polyolefins regarding chemical composition, irrespec tive of crystallinity. [6][7][8][9][10] HTIC uses graphitized carbon black as stationary phase and the separation is based on the selective interaction of long uninterrupted ethylene sequences with the graphitic surface.…”
Section: Doi: 101002/marc201700703mentioning
confidence: 99%
“…These techniques fractionate the macromolecules according to their crystallizability in solution and provide a predictable separation of the polymer fractions depending on the comonomer content, polymer chain irregularities, or tacticity differences. Such methods are still able to separate plastomers with densities between 902 and 910 kg m −3 according to their comonomer contents but are not suitable for elastomers with densities from 900 to 857 kg m −3 …”
Section: Introductionmentioning
confidence: 99%
“…Well‐established techniques working in solution such as crystallization fractionation (CRYSTAF), [ 25,26 ] temperature rising elution fractionation (TREF) [ 27 ] and Crystallization Elution Fractionation (CEF) [ 28,29 ] provide chemical composition based on crystallizability. [ 30–32 ] Regularly folded single crystals are the most stable polyethylene crystallite state in solution, in contrast, spherulites with amorphous regions are expected from melt crystallization.…”
Section: Introductionmentioning
confidence: 99%